Increased eryptosis in smokers is associated with the antioxidant status and C-reactive protein levels. (1st January 2019) - Attanzio, Alessandro; Frazzitta, Anna; Vasto, Sonya; Tesoriere, Luisa; Pintaudi, Anna Maria; Livrea, Maria Antonia; Cilla, Antonio; Allegra, Mario
Highlights: Cigarette smoking rise the levels of eryptotic erythrocytes in smokers. It also evokes an increase in CRP and a decrease in GSH in smokers. Trend to increase total leucocytes (inflammation) and forward scatter. Eryptotic erythrocytes linked with inflammatory and oxidative stress environment. Increased eryptosis in smokers potentially related to cardiovascular diseases. Abstract: Cigarette smoking has been linked with oxidative stress and inflammation. In turn, eryptosis, the suicidal erythrocyte death similar to apoptosis that can be triggered by oxidative stress, has been associated with chronic inflammatory diseases including atherosclerosis. However, the link between smoking and eryptosis has not been explored so far. The aim of the present study was to determine the level of eryptotic erythrocytes in healthy male smokers (n = 21) compared to non-smokers (n = 21) and assess its relationship with systemic inflammation (CRP) as well as with antioxidant defense (GSH) and their resistance to ex-vivo induced hemolysis. Smoking caused an increase in phosphatidylserine translocation outside the erythrocyte membrane (hallmark of eryptosis), significantly correlated to the plasma level of CRP (r = 0.546) and GSH concentration in erythrocytes (r=−0.475). With respect to non-smokers, smokers show a marginal increase of total leucocytes and erythrocyte volume, no modifications of the RBC resistance to oxidative stress-induced hemolysis and hematological and lipid parameters unvaried. We conclude that the inflammatory status (high CRP levels) and RBC oxidative stress (low GSH levels) caused by cigarette smoking are associated with an increase of eryptotic erythrocytes, a yet unknown relationship potentially involved with atherosclerosis and cardiovascular disease in smokers.